PERKEMBANGAN IKLIM DAN BUDAYA ORGANISASI DALAM STRUKTUR ORGANISASI MODERN - Ahmad Hariyadi (Jurnal Manajemen dan Penelitian Akuntansi (JUMPA), 2014)
Recent organization must realize that “change” as an ongoing prosess provides unpredictable opportunities as well as some confronting challenges. However,the need to change not depends solely to organisasi to organization‟s capacity to change. Moreover, it is also determined by the organizational environment besides the concepts of organizational climate and corporate culture. Both were regarded as valuable concepts if implemented properly in order to reach organizations‟ peak performance. This article described the development of organizational climate and corporate culture as time goes by and the type of recent organization‟s culture in modern organization. Therefore, the companies that delelop and maintain a fit and flexible corporate culture as well as organizational climate are more likely to be successful and profitable in encountering the challenges of the new millennium.